2011
DOI: 10.4103/0973-1482.80431
|View full text |Cite
|
Sign up to set email alerts
|

A survey of risk factors in carcinoma esophagus in the valley of Kashmir, Northern India

Abstract: Poor socio-economic status resulting in fewer intakes of fresh fruits, vegetables and fish in addition to heavy hookah smoking are suspected to be the major risk factors for the development of esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 12 publications
2
36
0
Order By: Relevance
“…11 Poor socio-economic status resulting in fewer intake of fruits and vegetables and fish and heavy hookah smoking are suspected to be the major risk factors for the development of esophageal cancer. 12 Drinking hot beverage over a period of time causing thermal injury leading to chronic esophagitis was strongly associated with a higher risk of esophageal cancer. 13 Various studies published previously on very high incidence of cancer esophagus in Kashmir have revealed wide spread contamination by N-nitroso compounds in raw food, salted tea prepared by adding sodium bicarbonate has shown high methanation activity and can cause endogenous formation of nitrosamines.…”
Section: Discussionmentioning
confidence: 99%
“…11 Poor socio-economic status resulting in fewer intake of fruits and vegetables and fish and heavy hookah smoking are suspected to be the major risk factors for the development of esophageal cancer. 12 Drinking hot beverage over a period of time causing thermal injury leading to chronic esophagitis was strongly associated with a higher risk of esophageal cancer. 13 Various studies published previously on very high incidence of cancer esophagus in Kashmir have revealed wide spread contamination by N-nitroso compounds in raw food, salted tea prepared by adding sodium bicarbonate has shown high methanation activity and can cause endogenous formation of nitrosamines.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of this cancer is higher in males and rises steadily with advancing age [6,11,12]. The current study also revealed a male preponderance with 59.47% of cases in the age group of 50-70 years Table 1.The patients usually present at an advanced stage with dysphagia to solids when more than half of the lumen gets involved with the disease.…”
Section: Discussionmentioning
confidence: 63%
“…Squamous cell cancer is the most prevailing histological subtype in the endemic regions of the world, accounting more than 90% of all esophageal malignancies [2].High incidence of cancer of esophagus has been reported from Caspian littoral of Iran, central and east Asia, certain areas of China [3]. In India cancer of esophagus is the most common malignancy involving the gastrointestinal track in Karnataka, Tamil Nadu,Kerala,Assam and Kashmir [4][5][6]. Despite advances in imaging technology and treatment modalities of carcinoma esophagus,5 year survival rates for patients with localized and regional involvement remain low at 33.7 and 16.7% respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Squamous cell carcinoma is the most prevalent histological form accounting over 90 % of cases in the endemic regions of the world. [3,4] The conventional treatment with surgery and radiation is limited with a five year survival of 10-25 % worldwide.…”
Section: Introductionmentioning
confidence: 99%